UJI PERFORMA AYAM KAMPUNG UNGGUL BALITNAK MENGGUNAKAN FORMULA PAKAN LUMPUR SAWIT TERFERMENTASI - Cindra Hubulo; Ellen J Saleh; Sri Suryaningsih Djunu (Jambura Journal of Animal Science, 2022)
The purpose of this study was to determine the performance of Kampung Unggul Balitnak (KUB) chicken fed palm mud fermented feed. Completely Randomized Design (CRD) was used in this study, with five treatments (5) and four replications (4). Each replication was placed 6 chickens aged 7 days. The results showed that the use of fermented palm sludge had no significant effect on feed consumption, body weight gain, and feed conversion value of KUB chickens. The use of fermented palm oil sludge in feed gives a good value to the performance of Kampung Unggul Balitnak (KUB) chickens.